Obliquity Dependence of Ocean Productivity and Atmospheric CO2 on Earth-like Worlds - Paul Lerner; Anastasia Romanou; Michael Way; Christopher Colose (The Astrophysical Journal)
Obliquity can shape the habitability of a planet by changing the seasonal availability of incident solar radiation. Changes in incident radiation can lead to changes in the availability of light, temperature, ocean circulation, stratification, and corresponding nutrient availability, all of which are important in determining ocean net primary productivity (NPP). Moreover, a fraction of the carbon assimilated by phytoplankton is sequestered in the deep ocean. Therefore, changes in productivity can alter the distribution of CO _2 between the ocean and atmosphere. In this study, we investigate the effects of obliquity on ocean NPP and the atmospheric CO _2 concentration using ROCKE-3D fully coupled to the NASA GISS Ocean Biogeochemistry Model. We find sea surface temperature primarily controls the NPP response, with both properties reaching a maximum at an obliquity of 45°. We find that the response of the seasonal amplitude of NPP to obliquity is controlled primarily by photosynthetically available radiation and secondarily by changes in nutrient availability. We also find that atmospheric CO _2 increases in response to obliquity, with a minimum at 15° and a maximum at 60°. The obliquity-driven CO _2 changes are controlled primarily by temperature-driven solubility changes, with circulation and biology either enhancing solubility-driven changes at low obliquities or acting against and partially offsetting solubility-driven changes at higher obliquities. The magnitude of obliquity-driven changes is likely too small to be detectable, though future studies are needed to determine whether changing obliquity simultaneously with other orbital parameters can lead to larger, potentially detectable changes in NPP and CO _2 .